Fully Biobased Aliphatic Anionic Oligoesters: Synthesis and Properties. (31st March 2019) - Kacem, Yosra Hadj; Bougarech, Abdelkader; Abid, Souhir; Abid, Majdi; Fleury, Etienne
Abstract : Biobased aliphatic sulfonated oligoesters with 10 to 30% of sulfonated units were synthesized by melt polycondensation of biobased monomers such as diethyl succinate, z-octadec-9-enedioic acid, dimer fatty acid, sodium (sulfonated dimethyl succinate), and various diols like 1, 4-butane diol and isosorbide. Structural characterization of the resulting oligoesters was determined by 1 H NMR spectroscopy and MALDI-TOF MS technique. Showing a regular structure, the nature of the different expected species present in the macromolecular structure allowed the detection of etherification and cyclisation side reactions. The study of the thermal properties indicates that the resulting oligoesters are amorphous or semicrystalline that essentially depend on the nature of monomers. Films of oligoesters treated in acidic, basic, and natural media at 37°C indicate that the remaining weight depends essentially on the composition of oligoesters. Finally, sulfonated oligoester was used to prepare a biobased poly(ester-urethane) thermoset, a material having tunable properties.